(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In this article, an attempt was made to explain in detail the approaches and methods of German language teachers to teach the learner the German language. Also, recommendations and instructions for use in the course of the lesson, as well as information on efficiency factors were provided.